Services Trade And Growth - Hoekman, Bernard M. 1959- (The World Bank, 2008)
The competitiveness of firms in open economies is increasingly determined by access to low-cost and high-quality producer services - telecommunications, transport and distribution services, financial intermediation, etc. This paper discusses the role of services in economic growth, focusing in particular on channels through which openness to trade in services may increase productivity at the level of the economy as a whole, industries and the firm. The authors explore what recent empirical work suggests could be done to enhance comparative advantage in the production and export of services and how to design policy reforms to open services markets to greater foreign participation in a way that ensures not just greater efficiency but also greater equity in terms of access to services